Imagining Ageing Representations of Age and Ageing in Anglophone Literatures (Edition 1) - Concilio, Carmen (transcript Verlag, 2018)
What do literary texts tell us about growing old? The essays in this volume introduce and explore representations of ageing and old age in canonical works of English and postcolonial literature. The contributors examine texts by William Shakespeare, Daniel Defoe, Julian Barnes, Thomas Kinsella, Seamus Heaney, J.M. Coetzee, Alice Munro, Witi Ihimaera and Patricia Grace and, together with a medical study, they suggest solutions to the challenges arising from the current demographic change brought about by ageing Western populations.